TINGKAT KEPUASAN IBU HAMIL TERHADAP PELAYANAN ANTENATAL - Rosmeri br bukit (LPPM Universitas Muhammadiyah Riau, 2017)
Satisfaction is the level of one’s feelings after comparing the permance perceived outcome with expectations. This research uses a quantitative with descriptive research design. The population in this study were all pregnant women antenatal checkups. Sample in this research were 30 respondents using technigues accidental. Analysis technique used is a univariate analysis. Based on the results obtained from the charging questioner satisfaction rate of pregnancy antenatal di Klinik Pratama Tangor Medical Centre (TMC) Pekanbaru found that the majority of the 30 respondent are satisfied as many as 21 people (70%). For Tangor Primer Klinik Medical Centre Pekanbaru complete room amenities approprite service standards for code of conduct applicable and treatment costs are covered by the patient.